Assessing the accuracy of complex refractive index retrievals from single aerosol particle cavity ring-down spectroscopy. Issue 10 (2nd October 2016) - Cotterell, Michael I.; Preston, Thomas C.; Orr-Ewing, Andrew J.; Reid, Jonathan P.
ABSTRACT: Cavity ring-down spectroscopy (CRDS) of single, optically manipulated aerosol particles affords quantitative retrieval of refractive indices for particles of fixed or evolving composition with high precision. Here, we quantify the accuracy with which refractive index determinations can be made by CRDS for single particles confined within the core of a Bessel laser beam and how that accuracy is degraded as the particle size is progressively reduced from the coarse mode (>1 μm radius) to the accumulation mode (<500 nm radius) regime. We apply generalized Lorenz–Mie theory to the intra-cavity standing wave to explore the effect of particle absorption on the distribution of extinction cross section determinations resulting from stochastic particle motion in the Bessel beam trap. The analysis provides an assessment of the accuracy with which the real, n, and imaginary, κ, components of the refractive index can be determined for a single aerosol particle. Published with license by American Association for Aerosol Research Abstract :